The role of adipokines in osteoporosis management: a mini review - Patil, Jayaditya Devpal; Fredericks, Salim (Frontiers in Endocrinology, 2024)
The prevalence of osteoporosis has been on the rise globally. With ageing populations, research has sought therapeutic solutions in novel areas. One such area is that of the adipokines. Current literature points to an important role for these chemical mediators in relation to bone metabolism. Well-established adipokines have been broadly reported upon. These include adiponectin and leptin. However, other novel adipokines such as visfatin, nesfatin-1, meteorin-like protein (Metrnl), apelin and lipocalin-2 are starting to be addressed pre-clinically and clinically. Adipokines hold pro-inflammatory and anti-inflammatory properties that influence the pathophysiology of various bone diseases. Omentin-1 and vaspin, two novel adipokines, share cardioprotective effects and play essential roles in bone metabolism. Studies have reported bone-protective effects of omentin-1, whilst others report negative associations between omentin-1 and bone mineral density. Lipocalin-2 is linked to poor bone microarchitecture in mice and is even suggested to mediate osteoporosis development from prolonged disuse. Nesfatin-1, an anorexigenic adipokine, has been known to preserve bone density. Animal studies have demonstrated that nesfatin-1 treatment limits bone loss and increases bone strength, suggesting exogenous use as a potential treatment for osteopenic disorders. Pre-clinical studies have shown adipokine apelin to have a role in bone metabolism, mediated by the enhancement of osteoblast genesis and the inhibition of programmed cell death. Although many investigations have reported conflicting findings, sufficient literature supports the notion that adipokines have a significant influence on the metabolism of bone. This review aims at highlighting the role of novel adipokines in osteoporosis while also discussing their potential for treating osteoporosis.